Julid dalam Perspektif Hadis - Ahmad Rudin; Muhammad Alif; Yetti Hasanah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This article aims to find out and understand about julid from a hadith perspective. Julid is an expression that has the meaning of being jealous of the success or enjoyment of other people. In slang, it is called julid, which is done by someone on social media by making comments, statuses or opinions that corner certain people. Meanwhile, this behavior is strictly prohibited by Islamic teachings. Therefore, the author will discuss julid in a hadith perspective. ThisLibrary research is a series of activities related to collecting library data, reading, recording, and processing research materials.